Design Method of Digital Signals’ Filter for Automatic Control Systems of Power Plant Equipment Operation - V. A. Janizki (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Method of digital signals’ filter characteristics is determined, obtained from power equipment control. They provide minimization of random noise influence by estimation parameters changes, determining the state of equipment and its operation. It is a different technique which allows to take into account the role of the main factors, determining control system’s efficiency: unequal influence of probability errors (1st and 2nd types) of equipment operation faults or their absence.